Dynamic Polarization of Rab11a Modulates Crb2a Localization and Impacts Signaling to Regulate Retinal Neurogenesis - Clark, Brian S.; Miesfeld, Joel B.; Flinn, Michael A.; Collery, Ross F.; Link, Brian A. (Frontiers in Cell and Developmental Biology, 2021)
Interkinetic nuclear migration (IKNM) is the process in which pseudostratified epithelial nuclei oscillate from the apical to basal surface and in phase with the mitotic cycle. In the zebrafish retina, neuroepithelial retinal progenitor cells (RPCs) increase Notch activity with apical movement of nuclei and the depth of nuclear migration correlates with the probability that the next cell division will be neurogenic. This study focuses on the mechanisms underlying the relationships between IKNM, cell signaling, and neurogenesis. In particular, we have explored the role IKNM has on endosome biology within RPCs. Through genetic manipulation and live-imaging in zebrafish, we find that early (Rab5-positive) and recycling (Rab11a-positive) endosomes polarize in a dynamic fashion within RPCs and with reference to nuclear position. Functional analyses suggest that dynamic polarization of recycling endosomes and their activity within neuroepithelia modulates the subcellular localization of Crb2a, consequently affecting multiple signaling pathways that impact neurogenesis including Notch, Hippo, and Wnt activities. As nuclear migration is heterogenous and asynchronous among RPCs, Rab11a-affected signaling within the neuroepithelia is modulated in a differential manner, providing mechanistic insight to the correlation of IKNM and selection of RPCs to undergo neurogenesis.